2015
DOI: 10.1093/scan/nsu160
|View full text |Cite
|
Sign up to set email alerts
|

Competition between frontoparietal control and default networks supports social working memory and empathy

Abstract: An extensive body of literature has indicated that there is increased activity in the frontoparietal control network (FPC) and decreased activity in the default mode network (DMN) during working memory (WM) tasks. The FPC and DMN operate in a competitive relationship during tasks requiring externally directed attention. However, the association between this FPC-DMN competition and performance in social WM tasks has rarely been reported in previous studies. To investigate this question, we measured FPC-DMN conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
89
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 59 publications
8
89
3
Order By: Relevance
“…Third, the representations within these various regions will need to be made consciously accessible, via selective broadcasting to the frontal-parietal networks described above. This selective broadcasting likely involves bidirectional interactions with regions of the DMPFC associated with affective working memory maintenance (Waugh et al, 2014), but also plausibly involves similar interactions with lateral frontal-parietal networks Xin and Lei, 2015). Therefore, while subcortical emotion circuits are important for generating these broad multifaceted emotional reactions, from the CN perspective, a phenomenological emotional experience involves considerable cortical contributions associated with representation of bodily sensations and their conceptual meaning, as well as cortical mechanisms associated with affective working memory and selective broadcasting.…”
Section: B3 Conscious Access To Emotionmentioning
confidence: 99%
“…Third, the representations within these various regions will need to be made consciously accessible, via selective broadcasting to the frontal-parietal networks described above. This selective broadcasting likely involves bidirectional interactions with regions of the DMPFC associated with affective working memory maintenance (Waugh et al, 2014), but also plausibly involves similar interactions with lateral frontal-parietal networks Xin and Lei, 2015). Therefore, while subcortical emotion circuits are important for generating these broad multifaceted emotional reactions, from the CN perspective, a phenomenological emotional experience involves considerable cortical contributions associated with representation of bodily sensations and their conceptual meaning, as well as cortical mechanisms associated with affective working memory and selective broadcasting.…”
Section: B3 Conscious Access To Emotionmentioning
confidence: 99%
“…Meanwhile, evidence from task-related neuroimaging revealed that extraversion is associated with the frontoparietal network [8,9] . Therefore, future studies should examine the relationships between these RSNs and personality traits when exploring the neuronal correlates of personality traits [57] .…”
Section: Perspectivesmentioning
confidence: 99%
“…When maintaining emotions seen in faces (as in Xin and Lei, 2015), for example, it seems there are at least three such strategies: (1) one could hold the visual image of the emotional face in mind, (2) one could label the face with an emotion word (e.g. “sad”) and then hold that word in mind or (3) one could imagine the emotional feeling itself and hold that feeling in mind 1 .…”
Section: Introductionmentioning
confidence: 99%